Manipulasi aktivitas riil pada perusahaan manufaktur: studi empiris di Bursa Efek Indonesia - Noor Endah Cahyawati; Nurtyas Mei Setiana (Jurnal Akuntansi dan Auditing Indonesia)
This study aims to empirically analyze the factors that influence management in manipulating real activities. The research design is a quantitative method using secondary data. The sample used in this study are 88 companies. Sample selection criteria used are manufacturing companies that have been included in the category of suspect companies during the period 2012-2016. The results of this study indicate that audit quality and managerial ownership have a significant positive effect on real activity manipulation, while the size of the audit committee, the proportion of independent commissioners, and institutional ownership have no influence on real activity manipulation. Limitations in this study is the use of real activity manipulation as the only dependent variable, so that further research can add other theoretical variables that can influence the practice of earnings management through manipulation of real activities, such as voluntary disclosures conducted by companies including CSR. The implication of this study, in running business operations does not focus primarily on current income or the achievement of profit targets to be achieved by manipulating real activities.